Evolution tendencies of Chinese underwater cultural heritage legislation in the new era: a legislative history study of China’s 2022 revision - Li, Qian; Qi, Xuewei (Frontiers in Marine Science, 2025)
Considering the fast development of Chinese deep-sea archaeology and the pressing situation of underwater cultural heritage (UCH), China’s legislation for UCH was revised again in 2022. This revision underwent a nine-year-long, arduous drafting process, but it has received little scholarly attention. This study explores the history of the revision via the comparison of four relevant legal documents to show the evolution of Chinese UCH legislation. The issues of most concern for China in the revision are the distribution of UCH responsibilities among different institutions, public participation, protection measures and international cooperation regarding UCH. In terms of the distance between Chinese legislation and the Convention on the Protection of the Underwater Cultural Heritage, three different types of evolution tendencies appeared in the revision history. First, China’s legislation moved continuously closer to the Convention, and this tendency is reflected in the issues of public participation, international cooperation and the distribution of UCH responsibilities. Second, with respect to protection measures, China’s law showed a hesitant tendency, as China’s legislation once moved closer to the Convention but eventually retrogressed. Third, with respect to the definition and ownership-based jurisdiction of UCH, China’s legislation did not make substantial changes and remained consistently far from the Convention. To explain the dynamic and arduous revision history, influencing factors in the “pull” and “push” directions are identified. The shift from a state-led protection model to an integrated model and the international context pushed China closer to the Convention, while the consideration of economic development and institutional conflicts pulled China back. Consequently, China ultimately made a compromise in 2022.